2017
DOI: 10.1007/s00125-017-4355-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterisation reveals active Wnt-signalling by human multipotent stromal cells as a key regulator of beta cell survival and proliferation

Abstract: Aims/hypothesis Novel strategies to stimulate the expansion of beta cell mass in situ are warranted for diabetes therapy. The aim of this study was to elucidate the secretome of human bone marrow (BM)-derived multipotent stromal cells (MSCs) with documented islet regenerative paracrine function. We hypothesised that regenerative MSCs will secrete a unique combination of protein factors that augment islet regeneration. Methods Human BM-derived MSCs were examined for glucose-lowering capacity after transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…Digested peptides were resuspended in 0.1% formic acid prior to label‐free LC/MS‐MS. Approximately 1 μg of each sample was injected onto a Waters M‐Class nanoAcquity HPLC system (Waters, Milford, Massachusetts) coupled to a Q Exactive Plus Orbitrap (Thermo Fisher Scientific, Waltham, Massachusetts) operating in positive mode, as previously described . Full MS parameters are outlined in the Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Digested peptides were resuspended in 0.1% formic acid prior to label‐free LC/MS‐MS. Approximately 1 μg of each sample was injected onto a Waters M‐Class nanoAcquity HPLC system (Waters, Milford, Massachusetts) coupled to a Q Exactive Plus Orbitrap (Thermo Fisher Scientific, Waltham, Massachusetts) operating in positive mode, as previously described . Full MS parameters are outlined in the Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently established active Wnt‐signaling as a characteristic of islet regenerative hMSC . To investigate whether pharmacological modulation of Wnt‐signaling during CM generation could further improve glycemic control after iPan CM‐injection, we sought to activate or inhibit basal Wnt‐signaling in hMSC using small molecules CHIR99201 or IWR‐1, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies on islet regeneration, transplantation of human bone marrow‐derived multipotent stromal cells (hMSC) induced the emergence of small, recipient‐derived islet‐like structures associated with the ductal epithelial niche . Detailed proteomic analysis of secretory factors deposited by hMSC revealed Wnt‐signaling as a central pathway in islet regenerative hMSC . Indeed, active Wnt‐signaling in hMSC generated conditioned media (CM) that increased β‐cell survival and proliferation in cultured human islets.…”
Section: Introductionmentioning
confidence: 99%
“…A collection of studies has demonstrated the potential of utilizing MSC as EV-generating biofactories and engineering the secretome of MSC to meet therapeutic needs 37,41,67 . Our previous studies have supported this progression of thought and we envision the creation of a cell-free biotherapeutics 'tailored' to combat a given pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological details of protein precipitation, digestion, liquid chromatography-tandem mass spectrometry, and proteomic data base analysis are described thoroughly in previous studies 13,36,37 . LC-MS/MS settings are outlined in Supplemental Table 2.…”
Section: Label-free Mass Spectrometry and Annotated Enrichment Analyses-mentioning
confidence: 99%